Construction of peptides encompassing multideterminant clusters of human immunodeficiency virus envelope to induce in vitro T cell responses in mice and humans of multiple MHC types. - Berzofsky, J A (1991)
To make synthetic peptide vaccines effective in a broad population of outbred humans, one would have to incorporate enough antigenic determinants to elicit recognition by T cells of most HLA types. We have previously defined multideterminant regions of the human immunodeficiency virus (HIV) envelope that include overlapping determinants seen by proliferating T cells of three or four haplotypes of mice. We have now tested the hypothesis that synthetic peptides encompassing such multideterminant regions will be recognized by T cells of multiple murine MHC types as well as by human T cells representing multiple HLA types. Six such peptides of 20-33 residues in length were prepared, and tested for their ability to stimulate T cells from mice of four distinct MHC types immunized with recombinant envelope protein rgp 160, as well as from 42 HIV-infected humans of different HLA types. Results identify several such peptides that are broadly recognized by mice of four H-2 types and by 52-73% of infected humans who still retain IL-2 productive responses to control recall antigens such as influenza A virus or tetanus toxoid. 86% of such infected donors tested against at least three peptides respond to at least one of the six peptides, and 77% of an additional group of seropositives respond to a mixture of the peptides. Moreover, the peptides can be used to immunize mice to elicit T cells reactive with the intact HIV envelope protein. These peptides therefore may be useful for both vaccine development in the broad human population, and diagnostic or prognostic use.